2018
DOI: 10.1177/0391398817752598
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking multilayers of poly-l-lysine and hyaluronic acid: Effect on mesenchymal stem cell behavior

Abstract: Owing to the precise control of polyelectrolyte multilayer properties such as potential, wettability, and viscoelasticity, the system presented here offers great potential for guided stem cell differentiation in regenerative medicine, especially in combination with materials exhibiting a defined surface topography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…This result was in agreement with previous work from other investigators . In case of samples treated with EDC‐NHS crosslinking no change was observed though coupling of carboxylic groups to amino groups should reduce the quantity of polar or charged groups exposed to the aqueous environment, which we found also for smooth multilayer films made of hyaluronan (HA) and poly‐ l ‐lysine (PLL) in a recent work . On the other hand, roughness of films increased, which will also decrease water contact angles according to Wenzel .…”
Section: Resultssupporting
confidence: 92%
“…This result was in agreement with previous work from other investigators . In case of samples treated with EDC‐NHS crosslinking no change was observed though coupling of carboxylic groups to amino groups should reduce the quantity of polar or charged groups exposed to the aqueous environment, which we found also for smooth multilayer films made of hyaluronan (HA) and poly‐ l ‐lysine (PLL) in a recent work . On the other hand, roughness of films increased, which will also decrease water contact angles according to Wenzel .…”
Section: Resultssupporting
confidence: 92%
“…For alizarin red‐S staining, cells were seeded on BMP‐2 loaded multilayers made on glass substrates, at a density of 50 000 cell mL −1 in DMEM 10% FBS+1% pen/strep and incubated for 14 days at 37 °C/5% CO2. Alizarin red‐S staining was performed as reported previously . Bright‐field images were taken using 10× lens via Leica DM IL microscope (Germany).…”
Section: Methodsmentioning
confidence: 99%
“…24 In another study we studied how polyelectrolyte multilayers (PEM) made of hyaluronic acid (HA) and poly-L-lysine (PLL), either as native or cross-linked system varying in elastic modulus, guide hADSC adhesion, growth, and differentiation. 37 We found that hADSC spread and grew more on stiffer, highly cross-linked than on soft native PLL/HA multilayers. It was also observed that hADSC moved towards the osteogenic lineage on stiffer and to adipogenic on soft, non-cross-linked multilayers.…”
Section: Introductionmentioning
confidence: 68%
“…Silicon wafers (Si-Mat, Germany) as model surfaces for PEM formation were cleaned before use with 'RCA clean 1' as previously described. 37 Briefly, ultrapure water and ammonia (25%, Roth, Germany) were mixed and heated to 75-80°C, and hydrogen peroxide (35%, Roth) was added to achieve a ratio of 5 : 1 : 1 (v/v/v). After 10 min incubation, the samples were excessively rinsed with ultrapure water (6 cycles of 5 min), dried with a stream of nitrogen, and used immediately.…”
Section: Surface Cleaningmentioning
confidence: 99%
See 1 more Smart Citation